Study the growth of microalgae in palm oil mill effluent waste water - Selmani, Nabila; Mirghani, Mohamed Elwathig Saeed; Alam, Md. Zahangir (2013)
This paper emphasizes mainly on the biomass productivity and lipid content of two microalgae strains known by their high lipid content namely: Botryoccocus sudeticus and Chlorella vulgaris. These starins were first screened for the highest biomass and lipid content, then Plackett-Burman design was used to evaluate the significant media for grown when using palm oil mill effluent (POME) waste water as culture medium. Results show that B. sudeticus contains high of biomass and lipids yield. Moreover, all three factors have positive effect on the biomass productivity, while using one nutrient factor gives moch lowerbiomass. These results can be used further as an insight for optimizing the biomass and the oil productivity of the microalgae.